Kemandirian belajar dalam mata pelajaran ilmu Pengetahuan sosial ditinjau dari motivasi belajar dan Lingkungan belajar siswa kelas viii Sekolah Menengah Pertama Negeri 1 Kunduran tahun ajaran 2015/2016 - Sunarto, Ricky; , Drs. Djumali, M.Pd (2016)
Ricky Sunarto. A210110050. Economic Accounting Education courses, Faculty of teacher training and educational sciences, University of Muhammadiyah Surakarta,2016. The purpose of this research is to find out: 1) To know the influence of learning motivation towards learning independence. 2) To know how the learning environment against the indepence of the study. 3) To know the influce of learning motivation and learning environment against the independence of the study. This research include quatitative research type associative with the withdrawal of the conclusion through an analysis of the statistics. The population in this research is the whole grade VIII SMP Negeri 1 Kunduran academic year 2015/2016. Samples taken is as much as 155 students with simple random sampling. Required data obtained via the question form and documentation. Previously the now tested and tested the validity and reliability. Data analysis technique used was multiple linear analysis, t-test, F-test, and the relative contribution and effective. The results of regression analysis regression line equation is obtained: Y= 16.025 + 0.202 X1 + 0.845 X2. The equation shows that the independence of learning is influenced by learning motivation and learning environment. The conclusion s drawn are; 1) Based on multiple linear regression analysis results obtained coefficient of 0.202 motivation, learning environment of learning and independence 0.845 amounting to 0.944, this prove that learning motivation variables and learning environment has an impact on the indepence of learning. 2) Of the test result obtained for t count variable learning motivation of 2.711 whereas t table of 1.960, then Ho denied that there is influence significant between learning motivation towards self reliance learn individually. 2) Of the test results obtained for t count variable learning environment of t table of 12.709 whereas 1.960, then Ho denied that there is influence significant between learning environment towards self-reliance learn individually. 3) From the results of analysis of the thest F retrieved F count = 148.840 > F table = 3.000, then Ho denied so together there is a significant influence on the learning motivation and learning environment against the independence of the study.